Բնական իրավունքի ազդեցությունը հայ իրավաքաղաքական ուսմունքների վրա - Կոչուբաև, Ալեքսանդր («ԱՐՑԱԽ» հրատ.)
Սույն հետազոտության նպատակն է վերլուծել բնական իրավունքի տեսության զարգացման նախադրյալները, ընթացքը և արդյունքները, նախանշել իրավունքի և պետության, անձի և քաղաքացիական հասարակության մասին ուսմունքի ընդհանուր տեսական և մեթոդաբանական զարգացման ուղղությունները, բնորոշել իրավական ուսմունքներում՝ համատեքստում հիմնարար բնական-իրավական կատեգորաների մշակման մեթոդաբանական հիմքերը և առանձնահատկությունը, բացահայտել բնական իրավունքի մասին պատկերացումների պատմական զարգացման հիմնական ուղենիշները և դրանց առանձնահատկությունները, ինչպես նաև վերլուծել բնական-իրավական հիմնահարցերի լուծման ձևերը նոր ժամանակի տարբեր ուղղությունների փիլիսոփայական-իրավական հայեցակարգերում։ The purpose of this study is to analyze the prerequisites, course and results of the development of the theory of natural law, to outline general theoretical and methodological directions for the development of the doctrine of law and the state, personality and civil society. To characterize the methodological foundations and specifics of the development of the main natural law categories in the context of legal doctrines, - to identify the main milestones in the historical development of ideas about natural law and their features, and also to analyze the ways of solving natural law problems in philosophical and legal concepts of various trends of Modern times. The methodological foundations of the research are the principles of a comprehensive analysis of political-legal and philosophical-legal doctrines. The study used logical, comparative legal, as well as historical, legal and comparative methods of cognition, which allowed the author to reveal the source of natural law ideas and their essence. In the course of the historical development of science in the system of teachings on law and the state, as well as in the ethical teachings of go, originating from the natural or divine order, or from the natural qualities of man, natural law acts as the basic concept. It is within the framework of the doctrine of natural law that legal science tries to find an answer to the question of the relationship between law and law, to understand that legal principles and norms are a special form of actual social relations, a unified form, in which there is an internal logic as an expression of the harmony of specific legal relations. Цель настоящего исследования ˗ проанализировать предпосылки, ход и результаты развития теории естественного права, наметить общие теоретические и методологические направления развития учения о праве и государстве, личности и гражданском обществе; охарактеризовать методологические основы и специфику развития основных естественно-правовых категорий в контексте правовых учений, -выявить основные вехи исторического развития представлений о естественном праве и их особенностях, а также проанализировать способы решения естественно-правовых проблем в философско-правовых концепциях различных направлений Нового времени. Методологические основы исследования составляют принципы комплексного анализа политико-правовых и философско-правовых учений. В исследовании использовались логический, сравнительно-правовой, а также исторический, юридически-сравнительный методы познания, что позволило автору раскрыть источник естественно-правовых идей и их сущность. В ходе исторического развития науки в системе учений о праве и государстве, а также в этических учениях го, происходящих из естественного или божественного порядка или из природных качеств человека, естественное право выступает в качестве основного понятия. Именно в рамках учения о естественном праве юридическая наука пытается найти ответ на вопрос о соотношении права и закона, понять, что правовые принципы и нормы являются особой формой фактических общественных отношений, унифицированной формой, в котором существует внутренняя логика как выражение гармонии конкретных правоотношений.
Keywords: Իրավագիտություն